2000
DOI: 10.4049/jimmunol.165.7.3951
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Human Monocyte IL-10 Concomitant to Minimal TNF-α Induction by Heat-Shock Protein 27 (Hsp27) Suggests Hsp27 Is Primarily an Antiinflammatory Stimulus

Abstract: Unlike more well-studied large heat shock proteins (hsp) that induce both T cell antiinflammatory (IL-10, IL-4) and macrophage proinflammatory (TNF-α, IL-15, IL-12) cytokines, hsp27, a small hsp, has been primarily identified as a substrate of mitogen-activated protein kinase-activated protein kinase-2 involved in the p38 signaling pathway and activated during monocyte IL-10 production. Hsp27 can also act as an endogenous protein circulating in the serum of breast cancer patients and a protein whose induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 45 publications
10
115
1
3
Order By: Relevance
“…JNK activation is also critical to DC maturation [34]. The reduced induction of MO JNK activity mediated by HSP-27 may explain its poor maturation of iDC vs. even low-dose LPS, which is a powerful JNK inducer [12,34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…JNK activation is also critical to DC maturation [34]. The reduced induction of MO JNK activity mediated by HSP-27 may explain its poor maturation of iDC vs. even low-dose LPS, which is a powerful JNK inducer [12,34].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that MO IL-10, and to a lesser extent TNF-a, can be induced by exogenous HSP-27 [12]. IL-10 as well as M-CSF can significantly impair differentiation of iDC from their precursors [14].…”
Section: Altered Cytokine or Mo Sensitivity To Differentiation Signalmentioning
confidence: 97%
See 3 more Smart Citations